Investigation into interactions of environmental and application time effects on 2, 4-D and dicamba-induced phytotoxicity and hydrogen peroxide formation. Issue 6 (November 2019) - Johnston, Christopher R.; Vencill, William K.; Grey, Timothy L.; Stanley Culpepper, A.; Henry, Gerald M.; Czarnota, Mark A.
Abstract: Application timing and environmental factors reportedly influence the efficacy of auxinic herbicides. In resistance-prone weed species such as Palmer amaranth ( Amaranthus palmeri S. Watson), efficacy of auxinic herbicides recently adopted for use in resistant crops is of utmost importance to reduce selection pressure for herbicide-resistance traits. Growth chamber experiments were conducted comparing the interaction of different environmental effects with application time to determine the influence of these factors on visible phytotoxicity and hydrogen peroxide (H2 O2 ) formation in A. palmeri . Temperature displayed a high degree of influence on 2, 4-D and dicamba efficacy in general, with applications at the low-temperature treatment (31/20 C day/night) resulting in an increase in phytotoxicity compared with high-temperature treatments (41/30 C day/night). Application time across temperature treatments significantly affected 2, 4-D–induced phytotoxicity, resulting in a ≥30% increase across rates with treatments at 4:00 PM compared with 8:00 AM. Temperature differential had a significant influence on dicamba efficacy based on visible phytotoxicity data, with a ≥46% increase with a high (37/20 C day/night) compared with a low differential (41/30 C day/night). Concentration of H2 O2 in herbicide-treated plants was 34% higher under a high temperature differential compared with the low differential. Humidity treatments and application time interactions displayed undetected or inconsistent effects on visible phytotoxicity and H2 O2 production. Overall, temperature-related influences seem to have the largest environmental effect on auxinic herbicides within conditions evaluated in this study. Leaf concentration of H2 O2 appears to be generally correlated with phytotoxicity, providing a potentially useful tool in determining efficacy of auxinic herbicides in field settings.